1997
DOI: 10.1029/97jd01569
|View full text |Cite
|
Sign up to set email alerts
|

Observing Earth's atmosphere with radio occultation measurements using the Global Positioning System

Abstract: Abstract. The implementation of the Global Positioning System (GPS) network of satellites and the development of small, high-performance instrumentation to receive GPS signals have created an opportunity for active remote sounding of the Earth's atmosphere by radio occultation at comparatively low cost. A prototype demonstration of this capability has now been provided by the GPS/MET investigation. Despite using relatively immature technology, GPS/MET has been extremely successful [Ware et al., 1996; Kursinski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
1,530
1
8

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,314 publications
(1,572 citation statements)
references
References 74 publications
33
1,530
1
8
Order By: Relevance
“…It follows very closely the Bönsch and Potulski (1998) formulation (at λ > 0.5 µm) and can be considered an improved version of the classical very similar optical refractivity formula developed by Edlén (1966). Different from the SmithWeintraub formula of microwave refractivity used in LMO (Schweitzer et al, 2011b), the water vapor term in this optical refractivity formula is essentially negligible because the frequencies are much too high for the permanent dipole moments of the water vapor molecules to contribute an orientation polarization term (the "wet term" in the microwave formula; e.g., Kursinski et al, 1997). The difference of the MW refractivity and the IR refractivity is illustrated over the range 2 µm to 3 µm by Schweitzer et al (2011a).…”
Section: Computation Of Ir Refractivity Impact Parameter and Altitudementioning
confidence: 99%
See 1 more Smart Citation
“…It follows very closely the Bönsch and Potulski (1998) formulation (at λ > 0.5 µm) and can be considered an improved version of the classical very similar optical refractivity formula developed by Edlén (1966). Different from the SmithWeintraub formula of microwave refractivity used in LMO (Schweitzer et al, 2011b), the water vapor term in this optical refractivity formula is essentially negligible because the frequencies are much too high for the permanent dipole moments of the water vapor molecules to contribute an orientation polarization term (the "wet term" in the microwave formula; e.g., Kursinski et al, 1997). The difference of the MW refractivity and the IR refractivity is illustrated over the range 2 µm to 3 µm by Schweitzer et al (2011a).…”
Section: Computation Of Ir Refractivity Impact Parameter and Altitudementioning
confidence: 99%
“…As described by Kirchengast and Schweitzer (2011), the LMIO method can be considered as a next generation of the well established and successful GNSS-LEO radio occultation (GRO) method (Ware et al, 1996;Kursinski et al, 1997;Steiner et al, 2001;Anthes et al, 2008;Luntama et al, 2008;Steiner et al, 2009;Ho et al, 2009). LMIO and GRO share the occultation measurement principle (Phinney and Anderson, 1968; and the use of highly coherent and stable inter-satellite signals, and therefore the potential of providing accurate, long-term, consistent benchmark data with high vertical resolution and global coverage.…”
mentioning
confidence: 99%
“…Detailed analyses of GNSS RO errors have been conducted by many scientists (Kursinski et al, 1997;Rieder and Kirchengast, 2001;Steiner and Kirchengast, 2005;ScherllinPirscher et al, 2011a, b). These errors mainly include the satellites' orbital error, clock biases, systematic hardware delay, antenna phase center variation, cycle slips, ionospheric refraction, atmospheric multipath and scintillations.…”
Section: Introductionmentioning
confidence: 99%
“…Global Navigation Satellite System (GNSS) radio occultation (RO) (Melbourne et al, 1994;Kursinski et al, 1997;Hajj et al, 2002) is a relatively new atmospheric remote sensing technique. It can deliver data traceable to the international standard of time (the SI second) and has the potential for monitoring decadal-scale climate change (Steiner et al, 2009;Scherllin-Pirscher et al, 2011b;Lackner et al, 2011) due to its unique characteristics such as high vertical resolution, high accuracy and long-term stability of its observations, as well as self-calibration capability and global coverage (Gobiet and Kirchengast, 2004;Steiner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…(1), we could see that a duct occurrence is usually accompanied by temperature inversion and/ or rapid decrease of moisture. Previous radiosonde refractivity studies pointed out that the most ducting events were found below 2 km [9,10]. Thus, the maximum computation height in this paper was limited to 2 km.…”
mentioning
confidence: 99%